2017
DOI: 10.1038/s41598-017-11848-z
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib suppresses extrahepatic metastasis de novo in hepatocellular carcinoma through inhibition of mesenchymal cancer stem cells characterized by the expression of CD90

Abstract: Cancer stem cells (CSCs) are a pivotal target for eradicating hepatocellular carcinoma (HCC).While considered monoclonal in origin, cancer is a heterogeneous disease in terms of morphology, biological behavior, chemo/radiation resistance, and prognosis. Traditionally, this heterogeneity has been attributed to the clonal evolution of tumor cells with the stochastic accumulation of genetic/epigenetic/genomic changes 1 . However, recent studies have suggested that cancer cell heterogeneity can also be explained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…Moreover, MDA-MB-231 cells induced to express high EPCAM were found to have reduced invasion phenotype [27]. Ha et al [28] and Yoshida et al [29] reported similar inhibition of migration and invasion in hepatocellular carcinoma cells after sorafenib treatment. In association with reduced migration and in- Breast cancer stem cells, responsible for cancer initiation, progression, chemoresistance and recurrence were identified as CD44 + /CD24 -/lo along with other markers such ALDH and CD49F [23,24,30].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, MDA-MB-231 cells induced to express high EPCAM were found to have reduced invasion phenotype [27]. Ha et al [28] and Yoshida et al [29] reported similar inhibition of migration and invasion in hepatocellular carcinoma cells after sorafenib treatment. In association with reduced migration and in- Breast cancer stem cells, responsible for cancer initiation, progression, chemoresistance and recurrence were identified as CD44 + /CD24 -/lo along with other markers such ALDH and CD49F [23,24,30].…”
Section: Discussionmentioning
confidence: 94%
“…Sorafenib inhibits the tyrosine phosphorylation of VEGFR-1, 2 and 3; PDGFR-β; Flt-3; and c-Kit [87]. Sorafenib is the priority drug used for advanced hepatocellular carcinoma (HCC) [65], as it inhibits the lung metastasis of HCC mediated by CD90 + cancer stem cells (CSCs) [66]. The combination of sorafenib and carfilzomib synergistically suppresses the metastasis of HCC via inducing tumor cell apoptosis [67].…”
Section: Tyrosine Kinase Inhibitor Therapymentioning
confidence: 99%
“…Li et al reported that 23.5% of patients with HCC (136 of 578 patients) had EHM prior to IHR (38.9%) after hepatectomy; the overall 5‐year survival rate in patients with EHM was 10.0%, which was significantly lower than that noted in patients who developed IHR alone (34.1%) 6 . Encouragingly, recent studies have demonstrated that sorafenib suppressed postoperative EHM and prolonged overall survival (OS) in patients with advanced HCC with EHM, thereby offering a potential option for postoperative adjuvant therapy to prevent EHM 4,9 . However, considering the confined efficacy in selected patients and intolerable side effects of sorafenib, 10‐12 the precise prediction of postoperative EHM is urgently needed to stratify patients for early prophylactic and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%